The effect of mindful parenting on gender-based violence: Father involvement as a mediator - Handayani, Arri; Ratnaningsih, Ika Zenita; Maulia, Desi; Widiharto, Chr. Argo; Bawono, Yudho (Psikohumaniora: Jurnal Penelitian Psikologi, 2024)
Gender-based violence (GBV) has increased in the last decade, highlighting the need for significant attention to the prevention of physical and/or sexual violence. This situation is partially influenced by parenting in the family and is specifically reinforced by the involvement of fathers. This study aims to examine the effect of mindful parenting on GBV, with the father's involvement in parenting as a mediator. Data were collected using accidental sampling from 739 people (503 women and 236 men) aged between 18 to 23 years old. The instruments used in the study were the Interpersonal Mindfulness in Parenting (IM-P) scale (31 items, α = .953); the Inventory of Father Involvement (IFI) (26 items, α = .915); and the Social Norms and Beliefs about Gender-based Violence (GBV) Scale (30 items, α = .935). Mediation analysis served to test the research hypothesis. The research results indicate that mindful parenting has a significant effect on GBV, with the direct effect (β = -0.244, p < .001) being lower than the indirect effect (β = -0.582, p < .001), and the results of the Sobel test (z = -11.649, p = .000, p < .001) suggest that this effect is mediated by the father's involvement in parenting. These findings emphasize the importance of increasing societal awareness regarding the significance of father involvement in parenting to reduce gender-based violence. Fathers should provide complete care by being physically and psychologically present, which could alleviate the mother's burden and diminish gender-based violence.